A Rare Complication of Thoracic Spine Surgery: Pediatric Horner's Syndrome after Posterior Vertebral Column Resection-A Case Report - Pawel Grabala; Kinga Danowska-Idziok; Ilkka J. Helenius (MDPI AG, 2023)
Background: Horner's syndrome (HS) classically consists of the symptom triad of miosis, ptosis, and anhidrosis. It is caused by impairment of a certain pathway in the sympathetic nervous system. It may also appear as part of the clinical signs of other diseases and syndromes, including Pancoast tumors, intradural and/or epidural tumors, thoracic outlet syndrome, syringomyelia, brachial plexus injury, and aortic dissection. Here, we report a very rare complication of vertebral column resection in children, and we present the clinical findings of a case of Horner's syndrome with a current literature review. Case presentation: A five-year-old child with severe congenital kyphoscoliosis qualified for surgical treatment of the spinal deformity via a posterior approach, with three-column osteotomy and fusion. Results: After successful surgery, the patient presented with HS due to distraction of the sympathetic nerve trunk and, thus, innervation to the left eye. At the 4-year follow-up, the child had fully recovered. Conclusions: Pediatric HS after posterior instrumented scoliosis correction surgery with posterior vertebral column resection of the thoracic spine is very rare. This is the first reported case of HS after posterior vertebral column resection and spinal fusion for congenital kyphoscoliosis without the use of epidural analgesia. Symptom resolution may be variable and, in some cases, delayed.